The adventures of Ook and Gluk : kung-fu cavemen from the future - Beard George (New York : Scholastic, 2010)
The world's most evil corporation of the future invades Caveland, Ohio and enslaves the inhabitants, until a time portal takes Ook and Gluk to the year 2222, where they meet a wise new friend who provides them with the means of saving the day.
"The second graphic novel by George Beard and Harold Hutchins"--Cover.
Keywords: Prehistoric peoples; Kung fu; Time travel; Factories; Businessmen; Beard, George (Fictitious character); Hutchins, Harold (Fictitious character); Prehistoric peoples; Kung fu; Time travel; Prehistoric peoples; Kung fu; Time travel